Solutions for Better Business Management – A Case in Brick and Ceramic Industry in Vietnam - HAI, NGUYEN THANH; DUONG, NGUYEN THUY (The journal of contemporary issues in business and government, 2021)
For better business performance we need to improve management. Business performance measurements can be done via many indicators such as stock price, profits. With the support of OLS linear regression, the paper aims to estimate effects from macro indicators on stock price in brick and granite ceramic sector, esp. in Taicera (TCR) in Vietnam? Our research found that between stock price of TCR and many macro factors there is negative correlation. Between stock price and Risk free rate (Rf) there is positive correlation. So, board need to enhance or forecast effects from macro policies on their stock price to manage the firm better. On the other hand, investors and institutions can refer to the model for prediction of stock price.